PROVINCIAL DISPARITIES IN THE BURDEN OF CARDIOVASCULAR DISEASES ATTRIBUTABLE TO GENERAL, ABDOMINAL AND VISCERAL ADIPOSITY: RESULT FROM A RECENT NATIONAL REPRESENTATIVE STUDY. (April 2021) - Kang, Yuting; Wang, Xin; Chen, Zuo; Jiang, Linlin; Zheng, Congyi; Yin, Peng; Dong, Wenlan; Zhang, Linfeng; Zhou, Maigeng; Wang, Zengwu; Gao, Runlin
Abstract : Objective: Recent data suggest that the burden of cardiovascular diseases (CVD) attributable to adipose differed by regions, while the disparity have not been fully discussed before in Chinese population. Figure. No caption available. Design and method: Data on participants aged 35 years or over selected from China Hypertension Survey (CHS) was used to calculate prevalence of adipose. Meanwhile, cohort data selected randomly from CHS was used to calculate the multivariable-adjusted HRs by Cox regression. HRs along with the adipose prevalence were used to calculate the PAF. Results: During a mean of 4.56 years of follow up, 1, 109 participants experienced at least a cardiovascular event. At national level, the PAF of CVD was 6.20 % [95% confidential interval (CI): 6.16%-6.24%] for overweight, 7.08% (95%CI: 6.99%-7.17%) for obesity, 13.30% (95%CI: 13.21%-13.37%) for abdominal obesity, 8.99% (95%CI: 8.94%-9.04%) for body fat percentage, and 5.14% (95%CI: 5.07%-5.21%) for visceral adipose index. At province level, the PAFs for obesity ranged from 13.31% in Tianjin to 2.37% in Hainan, from 20.78% in Tianjin to 5.38% in Hainan for abdominal obesity, with highest PAFs being in north and and west provinces, lowest in south and costal provinces. Conclusions: Our estimates are strikingly different across geographic regions, with a large proportion of CVD in China are attributable to adipose, including body fat percentage. Our findings support developing both national and provincially-specific strategies to reduce the burden of CVD and disparity in China.